2013
DOI: 10.1007/s10549-013-2724-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of tumor angiogenesis induced by desmopressin in a breast cancer model

Abstract: Desmopressin (DDAVP), a synthetic peptide analog of vasopressin, is a safe antidiuretic and hemostatic compound that acts as a selective agonist for the vasopressin V2 membrane receptor. It is known that DDAVP can inhibit progression of residual metastatic cells and also improves chemotherapy effects in preclinical breast cancer models. Here, we explored the effects of DDAVP on tumor angiogenesis using the aggressive F3II mammary carcinoma in syngeneic Balb/c mice. Intravenous administration of the compound (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 27 publications
4
50
0
Order By: Relevance
“…We attribute the tumor volume reduction to apoptosis induction. It could also be related to reduced angiogenesis, as previously demonstrated with breast cancer cells [1]. Desmopressin has been known to stimulate endothelial cells to release Von Willebrand factor (VWF) [12].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We attribute the tumor volume reduction to apoptosis induction. It could also be related to reduced angiogenesis, as previously demonstrated with breast cancer cells [1]. Desmopressin has been known to stimulate endothelial cells to release Von Willebrand factor (VWF) [12].…”
Section: Discussionmentioning
confidence: 83%
“…VWF plays a protective role against tumor cell dissemination and may cause apoptosis of micro metastatic foci. Data supporting this was collected from breast cancer in vitro and in vivo models, supporting anti angiogenic as well as cytostatic effects [1,14], and reduction of cancer cells in distant metastasis [14]. Endothelial V2 receptor activation could contribute to tumor reduction via angiogenesis inhibition and reduced VWF levels in tumor microenvironment.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Since we, and others [North, 2000;North et al 1998ab;Taylor et al, 1990;Ripoll et al 1990;Garona et al, 2015], have demonstrated that vasopressin action through V2 receptors is inhibitory to the growth of solid tumors, we have concluded that tumors probably manufacture AbnV2R as a null receptor to impair such growth inhibition. Since Alonso and coworkers [Ripoll et al, 2013;Garona et al,2015] have shown that activation of tumor V2 receptors seems to impair angiogenesis and tumor metastasis as well as retard growth of breast cancer, it is conceivable that all these mechanisms could also play some role in the inhibitory actions of Abner if the antibody internalizes and removes the null receptor and allows influences by tumor-generated vasopressin to be increased through normal V2 receptors. Treatments with Abner, instead of administering V2 receptor agonist proposed by Garona et al [2015] for breast cancer, would have the advantage of not exacerbating the condition of SIADH present in many cases of small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The potent hemostatic effects of dDAVP at relatively low doses of 0.2-0.3 µg/kg allows its use in the management of bleeding disorders and as a blood-saving agent during surgical procedures [8]. In addition, preclinical evidence has been accumulating on the antiangiogenic and antimetastatic properties of dDAVP at a higher dose range of 1-2 µg/kg in animal models of breast, prostate and colorectal cancer [9][10][11][12][13]. A recent clinical trial in breast cancer patients administered with perioperative infusions of dDAVP demonstrated a reduced intrasurgical bleeding with increasing doses of the compound.…”
Section: Introductionmentioning
confidence: 99%